2008
DOI: 10.1111/j.1530-0277.2008.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Sensitizes Cerebral Responses to the Odors of Alcoholic Drinks: An fMRI Study

Abstract: Background-Small, priming doses of alcohol enhance desire to drink, and thus play a role in the loss of control of alcohol consumption. Using functional magnetic resonance imaging (fMRI), we previously showed that alcoholic drink odors (AO; subjects' drinks of choice) induce greater nucleus accumbens (NAc) activity than non-appetitive odors (NApO; grass, leather) in subjects at risk for alcoholism. Here we hypothesized that priming exposure to alcohol would enhance responses to AO in the NAc and orbitofrontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 74 publications
5
78
2
Order By: Relevance
“…This finding is in line with previous research 1,21,70 showing an enhanced cueinduced brain response in this area, which may mediate an attentional bias toward drug cues. Interestingly, the observed brain response here is more superior than the previous finding from our group 1 ; this might be an effect of sample size or of differences in the covariables used for correction (local gray matter volume, as well as age, sex, smoking behavior, and mood effects).…”
Section: Commentsupporting
confidence: 82%
“…This finding is in line with previous research 1,21,70 showing an enhanced cueinduced brain response in this area, which may mediate an attentional bias toward drug cues. Interestingly, the observed brain response here is more superior than the previous finding from our group 1 ; this might be an effect of sample size or of differences in the covariables used for correction (local gray matter volume, as well as age, sex, smoking behavior, and mood effects).…”
Section: Commentsupporting
confidence: 82%
“…2 sLORETA contrast analysis before and after alcohol intake (P \ 0.05). a Alpha1, b alpha2, c beta3 and d gamma cortex, posterior cingulate cortex, retrosplenial area, and the precuneus are influenced by seeing or smelling alcohol cues (Bragulat et al 2008;Hermann et al 2006;Tapert et al 2003). Previous studies also showed that these brain areas, namely orbitofrontal cortex, ventromedial frontal cortex, subcallosal anterior cingulate cortex, posterior cingulate cortex, retrosplenial area, and the precuneus are also important in distress in general (Blood et al 1999;Damasio 1996;Dias et al 1996;Wheeler et al 1993) and also for tinnitus-related distress (Muhlau et al 2006;Vanneste et al 2010a).…”
Section: Discussionmentioning
confidence: 92%
“…subjects' drinks of choice) and non-appetitive odors (e.g. grass, leather) is characterized by activity in the orbitofrontal cortex, ventromedial frontal cortex, subcallosal anterior cingulate cortex, posterior cingulate cortex, retrosplenial area, and the precuneus in heavy drinkers (Bragulat et al 2008). Visual images of alcoholic beverages induced activity in the orbitofrontal cortex, ventromedial frontal cortex, and posterior cingulate (Hermann et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…No effect of parental alcoholism in processing of reward in the ventral striatum Bragulat et al (2008) Hazardous drinkers Increased limbic network activation to alcohol cues following small dose of alcohol Filbey et al (2008) Heavy drinking individuals Alcohol taste vs. appetitive control taste elicited response in the reward system (prefrontal cortex, striatum, ventral tegmental area ⁄ substantia nigra) Gilman and Hommer (2008) Treatment seeking alcohol-dependent patients vs. healthy controls Activation differences between the positive and negative as well as alcohol-related images among the alcoholics Myrick et al (2008) Nontreatment seeking alcohol-dependent individuals vs. social drinkers Naltrexone and ondansetron reduced alcohol cue-induced activation of the ventral striatum Beck et al (2009) Treatment seeking alcohol-dependent patients vs. healthy controls Link between high impulsivity and reduced ventral striatal activation to nondrug reward MRI Morphometry Jernigan et al (1991) Treatment seeking alcohol-dependent patients vs. healthy controls Increases in subarachnoid CSF volume and ventricular enlargement Pfefferbaum et al (1992) Treatment seeking alcohol-dependent patients vs. healthy controls…”
Section: Structural Gray and White Matter Changesmentioning
confidence: 99%